POWER RELATION IN THE TRANSCRIPTION OF SIMULATED POLICE INVESTIGATION: ergativity analysis - Windy Febrianingsih, - (2023)
Police investigation is one of the most important actions for successful crime detection and for revealing the truth of a case. During police investigation process, the police need to have a power to control the direction of questions in obtaining accurate information. In controlling the questions, the police might express the use of agents in their questions. Therefore, Halliday and Matthiessen's (2004) ergativity analysis was used to analyze the agents on the transcription of simulated police interviews. The research was conducted under a qualitative design. The data were used from the transcriptions of a simulated police interview in a domestic violence case. The result shows that the investigators used the agents in active voice as many as 62.6%, in passive 23.4% and in nominalization 14%. The investigators frequently used agents in the active voice, followed by passive voice and nominalization. Regarding those types of agents (agents in active voice, agents in passive voice, and agents in nominalization), there are two types of power relations in this research (positive power and negative power). The positive power might lead to a cooperative relationship between the investigators and interviewees, while negative power might lead to a coercive relationship.